AsbÄb Al-IkhtilÄf FÄ« TafsÄ«ri I Al-Salaf: Understanding the Reasons for Differences in Interpretation Among the Salaf Scholars - Nurfauziah, Anisa (UIN Sunan Gunung Djati Bandung, 2023)
This writing aims to understand the definition of ushul al-tafsir, tafsir, reference books of tafsir, its history, the legal aspects of studying tafsir, and its divisions. The research method employed in this study is library research and literature review. The results of this research reveal that the core subject matter is that tafsir explains the meaning of Quranic verses, the context of the story, and the reasons for the revelation of these verses using expressions that convey the apparent meaning. The practice of interpretation has existed since the time of the Prophet Muhammad and has evolved to the present day. In the study of tafsir, there are numerous sources or references as reading material, and it is highly recommended to study it. Tafsir can be divided into three categories, including considering what is known about the commentator, the approach used to attain it, and the methods of interpretation.